Comprehensive set of metrics for global food system analysis - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Published updated analytical framework to guide identification of relevant metrics and indicators based on data available in low-and-middle-income countries. Authors explain: with only minor additional investments, existing surveys could be adapted to cover a large part of required additional data, but for other indicators, targeted data collection efforts are needed.